2018
DOI: 10.1007/s00705-018-3735-8
|View full text |Cite
|
Sign up to set email alerts
|

Reduced antigen presentation capability and modified inflammatory/immunosuppressive cytokine expression of induced monocyte-derived dendritic cells from peripheral blood of piglets infected with porcine circovirus type 2

Abstract: The efficiency of immune responses and host defense against pathogens largely depends on the function of dendritic cells (DCs). Porcine circovirus type 2 (PCV2) infection causes viremia and extensive modulation of immune activities in the blood. The objective of the present study was to investigate the effects of PCV2 infection in vivo on the immunological function of DCs induced from peripheral blood monocytes (MoDCs). At different points after infection with PCV2, peripheral blood monocytes from PCV2-infecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 38 publications
0
9
0
1
Order By: Relevance
“…In our study, co-infection of two swine viruses (PCV2 and PPV) was assessed and the results showed a large frequency of both the viruses in domestic and free ranging pigs as well as in wild boars. Although further studies are needed to better characterize the PCV3 impact on the pig immune system, we can hypothesize that, by analogy with PCV2 whose immunosuppressive activity has already been demonstrated [37,38], PCV3 infection might compromise the swine immune system to a certain extent, thus facilitating concomitant infection with other common viruses. Indeed, conversely to what we observed, other authors found that even if co-circulation of PCV2 and PCV3 is a common occurrence in pig farms, co-infections of individual pigs seems to be rare [39].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, co-infection of two swine viruses (PCV2 and PPV) was assessed and the results showed a large frequency of both the viruses in domestic and free ranging pigs as well as in wild boars. Although further studies are needed to better characterize the PCV3 impact on the pig immune system, we can hypothesize that, by analogy with PCV2 whose immunosuppressive activity has already been demonstrated [37,38], PCV3 infection might compromise the swine immune system to a certain extent, thus facilitating concomitant infection with other common viruses. Indeed, conversely to what we observed, other authors found that even if co-circulation of PCV2 and PCV3 is a common occurrence in pig farms, co-infections of individual pigs seems to be rare [39].…”
Section: Discussionmentioning
confidence: 99%
“…SLA-typed pigs are used in vaccine design, disease models, and allogeneic and xenogeneic transplantation. of piglets infected with porcine circovirus type 2 (91). Based on GWAS analyses, Walker et al (92) verified that host genotype explained 64% of the phenotypic variation for overall PCV2 viral load, with two major quantitative trait loci (QTL), one identified on SSC7 near the SLA complex class II locus and, importantly, a missense mutation in the SYNGR2 on SSC12.…”
Section: Figurementioning
confidence: 99%
“…In vivo, PCV2 antigen has been found in macrophages, DC, and follicular dendritic cells [97,98,99]. A recent study focused on moDC generated from blood monocytes of PCV-2 infected pigs [100]. It was observed that PCV2 infection in vivo impaired DC functions: at the peak of virus proliferation (7 days post-infection), moDC generated from infected pigs presented reduced MHC II and CD80/86 expressions, lower levels of IL-10, IL-12, IL-8, MIP-1β, and reduced ability to stimulate T cells.…”
Section: Dendritic Cells and Virusesmentioning
confidence: 99%
“…It was observed that PCV2 infection in vivo impaired DC functions: at the peak of virus proliferation (7 days post-infection), moDC generated from infected pigs presented reduced MHC II and CD80/86 expressions, lower levels of IL-10, IL-12, IL-8, MIP-1β, and reduced ability to stimulate T cells. This DC dysfunction could be at least, in part, responsible for PCV2-induced immunosuppression [100]. Interactions of PCV2 with different DC subsets are summarized in Figure 5.…”
Section: Dendritic Cells and Virusesmentioning
confidence: 99%